2016
DOI: 10.5114/aic.2016.61641
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of coronary fractional flow reserve using contrast medium compared to adenosine

Abstract: IntroductionCoronary fractional flow reserve (FFR) is recommended as the gold standard method in evaluating intermediate coronary stenoses. However, there are significant debates concerning the agents and the timing of the measurement.AimTo compare the contrast medium induced Pd/Pa ratio (CMR) with the FFR.Material and methodsWe enrolled 28 consecutive patients with 34 intermediate lesions who underwent coronary FFR measurement by intracoronary (i.c.) adenosine. After baseline Pd/Pa was calculated, a single co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In a study by Topcu et al . cFFR correlated well with FFR ( r = 0.89) and showed good agreement in Bland-Altman analysis (mean bias was 0.027, 95% limits for agreement from –0.038 to 0.092) [ 22 ]. The CONTRAST study [ 12 ] compared the ability of cFFR vs. resting Pd/Pa and iFR to predict FFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Topcu et al . cFFR correlated well with FFR ( r = 0.89) and showed good agreement in Bland-Altman analysis (mean bias was 0.027, 95% limits for agreement from –0.038 to 0.092) [ 22 ]. The CONTRAST study [ 12 ] compared the ability of cFFR vs. resting Pd/Pa and iFR to predict FFR.…”
Section: Discussionmentioning
confidence: 99%
“…The CONTRAST study, comparing the ability of contrast medium Pd/Pa ratio (cFFR) to predict FFR versus resting indices, showed that cFFR was superior to resting Pd/Pa and iFR for predicting FFR while resting Pd/Pa and iFR provided equivalent diagnostic accuracy [ 12 ]. Several studies showed a good correlation of cFFR with FFR [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…All pressure tracings were standardized and centrally reviewed by a core laboratory. e other cFFR studies were of moderate quality due to their single-center design, small sample size, nonconsecutive population, and lack of a rigorous blinding method, which may be the source Cerrato et al [19] Johnson et al [4] Kanaji et al [16] Shiode et al [17] Topcu et al [15] Van Wyk et al [18] Leone et al [5] Study ID…”
Section: Discussionmentioning
confidence: 99%
“…Cerrato et al [19] Johnson et al [4] Kanaji et al [16] Shiode et al [17] Topcu et al [15] Van Wyk et al [18] Leone et al [5] 0.6 1.0 Sensitivity Q = 14.78, df = 6.00, p = 0.02 Emori et al [22] FAVOR Pilot [9] Stahli et al [30] WIFI II et al [21][25]…”
Section: Combinedmentioning
confidence: 99%
“…In the present issue of the journal another piece of evidence in favour of cFFR (also known as CMR, as in our previous RINASCI study) is presented [ 15 ]. The authors clearly confirmed previous reports also using manual injection of contrast medium, again supporting the wide applicability of this novel technique.…”
mentioning
confidence: 99%